The work-related stress experienced by registered nurses at municipal aged care facilities during the COVID-19 pandemic: a qualitative interview study - Cilmara Arén; Armand Jaçelli; Berit Gesar; Ingrid From (BMC, 2022)
Abstract Background Stress can originate from many different unsatisfying work situations. Registered nurses working in municipal care have experience of work-related stress in different ways. Aim The purpose of this study was to describe the work-related stress experienced by registered nurses caring for older people at municipal aged care facilities. Methods Qualitative semi-structured interviews according to Polit and Beck were carried out in clinical work at six different municipal aged care facilities in Sweden. Twelve registered nurses participated in the study. Results The results outlined in one main central theme: Feelings of inadequacy and dissatisfaction contribute to work-related stress and three categories: Difficulty coping with work tasks, Insufficient support, Work-related stress affects private lives. Areas identified were lack of time, staff shortages, high number of patients, lack of communication and teamwork in the working group, showing that inadequacy and dissatisfaction can contribute to work-related stress. This can contribute to work-related stress, and it can be a result of problems in the organizational and social work environment. Conclusion This study showed the everyday experiences of registered nurses' stress at work. The reasons that registered nurses experience a heavy workload were found to be similar in several municipal care facilities. Future interventions should consider the areas of stress found in this study to reduce the risk of further increasing the work-related stress experienced by registered nurses working in municipal aged care.